Sward characteristics and herbage accumulation of Tanzania grass submitted to sward heights - Canto, Marcos Weber do; Jobim, Clóves Cabreira; Gasparino, Eliane; Hoeschl, André Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to evaluate different sward height (20, 40, 60 e 80 cm) in Tanzania grass (Panicum maximum Jacq.) pastures managed under continuous stocking. The animals used were Nellore steers, and the control of sward height was done with put-and-take techniques. Evaluations were made for: forage mass, green leaf mass, leaf:stem ratio, morphological composition and dry matter accumulation rate. The experimental design was completely randomized with two replications. Forage mass increased linearly with sward height with overall mean of 2,767, 3,105, 3,657 and 4,436 kg ha-1 at sward heights 20, 40, 60 and 80 cm, respectively. Rates of dry matter accumulation decreased with increasing sward heights and were 104, 108, 90 and 81 kg ha-1 per day for sward heights 20, 40, 60 and 80 cm, respectively. Leaf:stem ratio decreased linearly with sward heights. Tanzania grass pastures, under continuous stocking, should be managed between 40 and 60 cm heights in the final of spring and during summer station.